TREND OF TYPE 1 DIABETES MELLITUS IN BOYS AND GIRLS UNDER 14 YEARS OF AGE IN BELGRADE IN THE PERIOD FROM 1992 TO 2017: JOINPOINT REGRESSION ANALYSIS - Nikolic, Aleksandra; Majcan, Marta; Grujicic, Sandra (HEALTH CARE, 2020)
Introduction/Aim: Type 1 diabetes (DM1) is one of the most common chronic diseases of childhood and adolescence. The incidence of DM1 in children and adolescents has increased worldwide. The aim of this study was to analyze the trend of DM1 in boys and girls aged 0-14 years in Belgrade during period 1992-2017. Methods: Data on the number of children with diabetes for the period 1992-2017 were obtained from two hospitals, the Institute for Mother and Child Dr Vukan Cupic and the University Children’s Hospitals, as well as from the registers. Belgrade population figures are official data from the Statistical Office of The Republic of Serbia. Based on the data obtained, crude, standardized and age-specific incidence rates of DM1were calculated. Results: In Belgrade in the period 1992-2017 the average standardized incidence rate (per 100,000) is 13.9 for boys and 12.3 for girls aged 0-14 years. In both sexes, the age-specific incidence rate of DM1 increases with age and is highest at the age of 10-14 years. In the observed period of 26 years, there was a significant average annual increase in the standardized incidence rate of DM1 of + 3.3% in boys and + 3.1% in girls. In boys, a significant average annual increase in the age-specific incidence rate of DM1 was at the age of 5 to 9 years (+ 5.1%), and in girls in the age group 0-4 years (+ 12.9%). Conclusion: A further follow-up of DM1 in children aged 0-14 years is needed in order to identify risk factors that contribute to the development of this disease and to take adequate preventive measures, as well as to organize the health care.